Method and program model of microelectromechanical systems components synthesis based on genetic algorithm and ontology models - Vasyliuk, Ia.; Teslyuk, V.; Denysyuk, P. (Видавництво Львівської політехніки, 2013)
In this paper the general process and the concurrent synthesis realization model of microelectromechanical systems, which is based on developed genetic algorithm, are described. As the synthesis task in the sphere of complex microsystems is very comprehensive and timeconsuming, the actuality of performance and speed issues to generate the novel system and its components constructions is still up-to-date unsolved item. The developed model facilitates and accelerates the synthesis of the new and unique microelectromechanical systems structures.ontology, genetic algorithm (GA), stochastic methods, concurrency. Описано загальний процес і паралельну модель реалізації синтезу мікроелектромеханічних систем, що ґрунтуються на розробленому генетичному алгоритмі. Оскільки завдання синтезу у сфері комплексних мікросистем є дуже складним у своїй структурі і затратним у часі, актуальність питань виконання і швидкості, щоб згенерувати новітню систему і її структурні компоненти, є все ще невирішеною сьогодні. Розроблена модель сприяє і прискорює синтез нових і унікальних мікроелектромеханічних структур системи.
Keywords: microelectromechanical systems (MEMS); computer-aided systems (CAD); ontology; genetic algorithm (GA); stochastic methods; concurrency; мікроелектромеханічні системи (МЕМС); системи автоматизованого проектування (САПР); онтологія; генетичний алгоритм (ГА); стохастичні методи; паралелізм